Emergency department based intervention with adolescent substance users: 10 year economic and health outcomes - Tait, Robert; Teoh, L.; Kelty, E.; Geelhoed, E.; Mountain, D.; Hulse, G. (Elsevier Ireland Ltd, 2016)
BACKGROUND: Alcohol and other drug (AOD) use are significant cause of disease burden and costs among adolescents. METHODS: We conducted a randomized trial in hospital emergency departments (ED) following an AOD-related presentation, comparing usual care with brief advice and referral to link adolescents aged 12-19 years with external AOD services. Subsequently, we used health data linkage to assemble data on mortality, hospital admissions, ED attendances, out-patient mental health and use of opiate pharmacotherapies in the next 10 years. From these, treatment costs and rates of events were estimated and compared using generalized linear models. RESULTS: Those who received the intervention had lower costs ($22 versus $227: z=3.16, p=0.002) and rates (0.03 versus 0.25: z=2.57, p=0.010) of ED mental health AOD presentations. However, the intervention did not significantly reduce overall mean health costs per patient (intervention $58746 versus control $64833, p=0.800). Similarly, there was no significant difference in the costs associated with hospitalizations ($48920 versus $50911 p=0.924), overall ED presentations ($4266 versus $4150, p=0.916), out-patient mental health services ($4494 versus $7717, p=0.282), or opiate pharmacotherapies ($1013 versus $2054, p=0.209). Injecting drug use was a significant baseline predictor of subsequent costs in the cohort (z=2.64, p=0.008). CONCLUSIONS: An ED delivered intervention may reduce direct ED costs and subsequent ED AOD attendances. There was also some indication that overall costs may be impacted, with economically large but non-significant differences between the groups. The high costs and morbidity incurred by some of this cohort illustrate the importance of targeting high-risk adolescents.